A changing ethnic landscape? The effect of refugee immigration on inter-ethnic group relations and identities of previous immigrants - Renate Gabriele Lorenz (Deutsches Institut für Wirtschaftsforschung (DIW), German Socio-Economic Panel (SOEP), 2025)
How does the arrival of a new immigrant group affect earlier generations of immigrants? Do intergroup relations and self-identification among earlier immigrants change? Previous research on ethnic boundaries is usually restricted to a twogroup paradigm and primarily focuses on the majority group's perspective. In contrast, this study analyzes how the arrival of refugees in Germany influenced previous immigrants of Turkish and Polish origin by exploiting regional and temporal variation in refugee immigration. I combine macro data about refugees with individual longitudinal data of a large-scale German panel survey (SOEP) from 2012 to 2018 based on a random sample. Using fixed effects estimations, this study finds that an increasing proportion of refugees in a county increased concerns about immigration and decreased self-reported discrimination among respondents of Turkish (N = 676 respondents, n = 2,914 person-years) and Polish (N = 513 respondents, n = 2,141 person-years) origin. Moreover, immigrants of Turkish origin tended to feel more German while simultaneously feeling closer to Turkey. Immigrants of Polish origin also felt more German but not closer to Poland. These results are in line with the theoretical assumptions that minority groups tend to distance themselves from new immigrants, and use the opportunity to improve their own social position by strengthening their identification with the majority and/or with their own ethnic group.
Keywords: 330